TOXICITY TO Artemia salina AND PHYTOCHEMICAL COMPONENTS OF Thalassia Hemprichii SEAGRASS ON NIRWANA BEACH PADANG CITY WEST SUMATERA PROVINCE - Arifin, Adani Fatahilal; Nurrachmi, Irvina; Efriyeldi, Efriyeldi (Jurnal Perikanan dan Kelautan, 2020)
Many of marine ecotourism activities on Nirwana Beach has had a negative impact to the development of seagrass ecosystems. Pressure that occurs on the coastal ecosystem becomes a trigger factor seagrasses to adapt with produce certain compounds for maintain immunity, the name is bioactive compounds. This research was aimed to know toxicity to Artemia salina and phytochemical component of Thalassia hemprichii seagrass from Nirwana Beach by using experimental method. Two seagrass extracts with different solvents have been made in the Marine Chemistry Laboratories for use in toxicity and phytochemical tests. The results of the test are displayed in tabular or graphical form and analyzed descriptively. The results of toxicity testing showed that seagrass had a toxicity level of 446.872 ppm (n-hexane solvent) and 218.183 ppm (methanol solvents), both of extract are toxic to the Artemia salina. Phytochemical testing shows tannin compounds founded in extracts with n-hexane and methanol solvent, alkaloids and triterpenoids compound contained in extracts with methanol solvent.